Labor Migration and Welfare in the Kyrgyz Republic (2008-2013) - World Bank Group (World Bank, Washington, DC, 2015)
This paper examines the impact of labor migration from a welfare and social development perspective. Rather than focusing on regulatory and legal aspects determining migration, this note centers on the impacts of migration on the domestic welfare of households in the Kyrgyz Republic. The profiling of labor migration and identification of knowledge gaps are used to inform the development of strategies for more effective and sustainable welfare impacts from labor migration and remittances.